Manual therapy and exercise effects on inflammatory cytokines: a narrative overview - Cook, Chad E.; Keter, Damian; Cade, William Todd; Winkelstein, Beth A.; Reed, William R. (Frontiers in Rehabilitation Sciences, 2024)
Initiative. 10,and 12) have gained a significant amount of interest in their potential role in persistent pain for musculoskeletal (MSK) conditions.Manual therapy (MT) and exercise are two guideline-recommended approaches for treating MSK conditions. The objective of this narrative overview was to investigate of the effects of MT and exercise on pro-and anti-inflammatory cytokines and determine the factors that lead to variability in results. Methods: Two reviewers evaluated the direction and variabilities of MT and exercise literature. A red, yellow, and green light scoring system was used to define consistencies. Results: Consistencies in responses were seen with acute and chronic exercise and both pro-and anti-inflammatory cytokines. Chronic exercise is associated with a consistent shift towards a more anti-inflammatory cytokine profile (Transforming Growth Factor-beta, and Interleukin-2 and 13, whereas acute bouts of intense exercise can transiently increase proinflammatory cytokine levels. The influence of MT on cytokines was less commonly studied and yielded more variable results. Conclusion: Variability in findings is likely related to the subject and their baseline condition or disease, when measurement occurs, and the exercise intensity, duration, and an individual's overall health and fitness.